(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: The advantageous effect of physical activity stimulated mostly by aerobic exercise known to impact the particular phases of brain activities. Exercise does help to improve physical health and develop an individual’s academic performance. Aim and objectives: The study aimed to observe the relationship between type and duration of exercise on the mental, physical health, and academic performance of undergraduate medical students. Materials and method: Present questionnaire-based study was undertaken on 50students of medical undergraduates studying in their preliminary MBBS curriculum. Results: Among the participants involved in regular exercise, 50% of them prefer jogging, brisk walking, or cycling as a mode of exercise, followed by 31% of participants who prefer to play various games that involve muscular activities. The remaining 19% of the students like to be involved in multiple activities of the gym. 84% of participants with regular exercise practice gave a strong opinion that they are confident enough to face academic assessment challenges. This observation was notably higher prevalence than that of non-exercise students (79%). Conclusion: Individuals who exercise for one to two hours have better physical and mental health status and excellent academic performance. It can also be concluded that students who do regular exercise have higher confidence in academics than those who do not. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 135-139